2010
DOI: 10.4244/eijv6i2a37
|View full text |Cite
|
Sign up to set email alerts
|

The twelve-month outcomes of a biolimus eluting stent with a biodegradable polymer compared with a sirolimus eluting stent with a durable polymer

Abstract: Aims: This study reports the 12-month clinical outcomes of the LEADERS clinical trial which compared a biolimus eluting stent with a biodegradable polymer (BES) to a sirolimus eluting stent with a durable polymer (SES). Methods and results:The multicentre LEADERS trial employed an all-comers approach to recruit 1,707 patients who were randomised to treatment with either BES (n=857) or SES (n=850) in a noninferiority design. The primary clinical endpoint of this study was a composite of cardiac death, myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…[13][14][15][16][17] Trials have revealed the lower rates of MACE in short-and long-term follow-up after the DP-EES implantation in comparison to the earlier generation and have introduced the DP-EES as the standard of DES, versus other design improvements. 18 Investigators have also confirmed the superiority of the BP-BES over the first-generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Trials have revealed the lower rates of MACE in short-and long-term follow-up after the DP-EES implantation in comparison to the earlier generation and have introduced the DP-EES as the standard of DES, versus other design improvements. 18 Investigators have also confirmed the superiority of the BP-BES over the first-generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, alternative degradable coatings were developed to avoid a permanent polymer-mediated inflammatory stimulus on the vessel wall (48,49). However, the long-term reliability of degradable polymer coatings in accelerating re-endothelialisation and optimising vascular healing still needs to be proven.…”
Section: Simsekyilmaz Et Al Coronary Interventionsmentioning
confidence: 99%
“…The durable polymer in first generation stents may be one of the causes of incomplete endothelisation [53]. The BIOMATRIX stent is stainless steel and elutes Biolumis, a sirolimus analogue, combined with an abluminal poly-Llactide polymer that biodegrades within six to nine months [41].…”
Section: Biolimus Eluting Stents With Biodegradable Polymermentioning
confidence: 99%